A neurocognitive perspective on retrieval interference in L2 sentence processing. Issue 4 (1st August 2016) - HAMRICK, PHILLIP; ULLMAN, MICHAEL T.
Abstract : Cunnings (Cunnings) offers an interpretation of L2-L1 sentence processing differences in terms of memory principles. We applaud such cross-domain approaches, which seem likely to significantly elucidate the neurocognition of language. Cunnings attributes sentence processing differences between (adult) high proficiency L2 and L1 speakers to an increased susceptibility to similarity-based retrieval interference, rather than to qualitative L2-L1 processing differences (cf. Clahsen & Felser, 2006 ). On his account, both L1 and L2 sentence processing depend upon a 'bipartite' working memory, which involves maintaining items active by focusing attention on long-term memory representations (Cowan, 2001 ).